Preliminary Investigation of the Treatment of Equine Medial Femoral Condylar Subchondral Cystic Lesions With a Transcondylar Screw. Issue 3 (16th May 2014) - Santschi, Elizabeth M.; Williams, Jarred M.; Morgan, Joseph W.; Johnson, Christopher R.; Bertone, Alicia L.; Juzwiak, James S.
<x xml:space="preserve">Abstract</x> Objective To determine if medial femoral condylar (MFC) subchondral cystic lesions (SCL) causing lameness will demonstrate radiographic evidence of healing and lameness reduction after placement of a transcondylar screw in lag fashion. Study Design Retrospective case series. Animals Horses (n = 20) with lameness attributed to a MFC SCL. Methods A 4.5 mm screw was inserted in lag fashion across MFC SCL in horses with hindlimb lameness. Post‐operative radiography and lameness examinations were performed at 30–60 day intervals after surgery for 120 days, and SCL radiographic area and lameness were graded. Treatment was considered successful if lameness was eliminated and the radiographic area of the SCL on a caudocranial projection decreased ≥50% by 120 days. Results Twenty‐six limbs were treated. Nine horses (11 limbs) had autologous adjunctive biologics placed into the SCL. Lameness was reduced by 1–2 grades by 60 days after surgery in 18 horses and was eliminated in 15 horses by 120 days, at which time the SCL area had decreased ≥50% and work had resumed without lameness (mean follow‐up, 12 months). Biologic therapies had no impact on treatment success. Treatment was less successful in horses >3 years of age. Conclusions A MFC transcondylar screw decreases the area of a MFC SCL on craniocaudal radiographs and eliminates lameness in ∼75% of horses by 120 days. The simplicity and lack of specialized equipment required make this technique a useful option for the treatment of equine SCL causing lameness.